2013
DOI: 10.1093/toxsci/kft188
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Atg5-Dependent Autophagic Flux Promotes Paraquat- and MPP+-Induced Apoptosis But Not Rotenone or 6-Hydroxydopamine Toxicity

Abstract: Controversial reports on the role of autophagy as a survival or cell death mechanism in dopaminergic cell death induced by parkinsonian toxins exist. We investigated the alterations in autophagic flux and the role of autophagy protein 5 (Atg5)-dependent autophagy in dopaminergic cell death induced by parkinsonian toxins. Dopaminergic cell death induced by the mitochondrial complex I inhibitors 1-methyl-4-phenylpyridinium (MPP⁺) and rotenone, the pesticide paraquat, and the dopamine analog 6-hydroxydopamine (6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 130 publications
9
57
0
Order By: Relevance
“…cancer and neurological and neurodegenerative disorders, such as Parkinson and Alzheimer disease) (25,27,28). Recent studies have found that several environmental toxicants, such as arsenic (29), cadmium, chromium (30,31), dibenzofuran (32), paraquat (33), and ethanol (34,35), cause alterations in the basal levels of autophagy, leading to cellular toxicity. Autophagy acts as a cardinal process and interconnects several cell survival pathways (viz.…”
Section: Bisphenol-a (Bpa)mentioning
confidence: 99%
“…cancer and neurological and neurodegenerative disorders, such as Parkinson and Alzheimer disease) (25,27,28). Recent studies have found that several environmental toxicants, such as arsenic (29), cadmium, chromium (30,31), dibenzofuran (32), paraquat (33), and ethanol (34,35), cause alterations in the basal levels of autophagy, leading to cellular toxicity. Autophagy acts as a cardinal process and interconnects several cell survival pathways (viz.…”
Section: Bisphenol-a (Bpa)mentioning
confidence: 99%
“…As previously reported [4,15,34,35], acute paraquat challenge promoted apoptosis and mitochondrial injury. To understand the impact of ET A knockout on paraquat exposure-induced apoptosis and mitochondrial injury, if any, apoptosis and mitochondrial function were assessed using caspase-3 activity and aconitase assays, respectively.…”
Section: Et a Knockout Attenuates Paraquat-induced Apoptosis And Mitosupporting
confidence: 82%
“…The dopaminergic properties of the neuroblastoma cell line SK-N-SH and their cell culture have been detailed before (Garcia-Garcia et al, 2013). Wild type (WT), double knockout AMPK (DKO-AMPK −/− ) and Ulk1 knockout (Ulk1 −/− ) mouse embryonic fibroblasts (MEFs) were kindly provided by Dr. Mondira Kundu (St. Jude Children’s Research Hospital) and Dr. Benoit Viollet (Institut Cochin INSERM) (J.…”
Section: Methodsmentioning
confidence: 99%